Is Spinal Anesthesia Safer than General Anesthesia for Patients Undergoing Revision THA? Analysis of the ACS-NSQIP Database. Issue 1 (January 2020) - Wilson, Jacob M.; Farley, Kevin X.; Bradbury, Thomas L.; Guild, George N.
Abstract: Background: The incidence of revision THA continues to increase and there is a need to identify risk factors contributing to postoperative complications. Anesthesia type has been shown to be associated with complication rates in patients who undergo primary THA, but it is not clear whether the same is true among patients undergoing revision THA. Questions/purposes: (1) After controlling for confounding variables, in the setting of a large-database analysis, is spinal anesthesia associated with a lower risk of death, readmission, reoperation, postoperative transfusion, thromboembolic events, surgical site infection (SSI), and re-intubation among patients undergoing revision THA? Methods: The American College of Surgeons-National Surgical Quality Improvement (ACS-NSQIP) database was queried for patients undergoing aseptic, revision THA with either spinal or general anesthesia. Coarsened exact matching was used to match patients based on several baseline characteristics, including age, sex, body mass index, surgery type (Current Procedural Terminology code), and the modified Frailty Index score. Coarsened exact matching is a statistical method of exact matching that matches on chosen characteristics, in which continuous variables may be temporarily coarsened (such as, into discrete categorical variables) to facilitate matching. This method is an alternate to and requires less estimation than traditional propensity score matching. Then, using a model controlling for baseline patient characteristics and operative time, we performed multivariate logistic and linear regression analyses of matched cohorts to examine differences in mortality, readmission, reoperation, thromboembolic events, transfusion, SSI, and re-intubation. Results: After statistical matching and controlling for baseline demographic variables, surgery type (one- or two-component revision), surgical time and modified Frailty Index we found that patients receiving general anesthesia had higher odds of mortality (OR 3.72 [95% CI 1.31 to 10.50]; p = 0.013), readmission (OR 1.49 [95% CI 1.24 to 1.80]; p < 0.001), reoperation (OR 1.40 [95% CI 1.13 to 1.73]; p = 0.002), thromboembolic events (OR 2.57 [95% CI 1.37 to 4.84]; p = 0.003), SSI (OR 1.32 [95% CI 1.01 to 1.72]; p = 0.046), postoperative transfusion (OR 1.57 [95%CI 1.39 to 1.78]; p < 0.001) and unplanned intubation or failure to wean off intubation (OR 5.95 [95% CI 1.43 to 24.72]; p = 0.014). Conclusions: In patients undergoing revision THA, spinal anesthesia is associated with a decreased risk of several complications. The current investigation suggests that, when practical (such as when long surgical times or changes to the surgical plan are not anticipated), spinal anesthesia should be considered for use during revision THA. Level of Evidence: Level III, therapeutic study.